2018
DOI: 10.3389/fpsyg.2018.02081
|View full text |Cite
|
Sign up to set email alerts
|

Using Hierarchical Linear Models to Examine Approximate Number System Acuity: The Role of Trial-Level and Participant-Level Characteristics

Abstract: The ability to intuitively and quickly compare the number of items in collections without counting is thought to rely on the Approximate Number System (ANS). To assess individual differences in the precision of peoples’ ANS representations, researchers often use non-symbolic number comparison tasks in which participants quickly choose the numerically larger of two arrays of dots. However, some researchers debate whether this task actually measures the ability to discriminate approximate numbers or instead meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 89 publications
1
10
0
Order By: Relevance
“…There was a ratio effect on accuracy for fully incongruent trials, but not for congruent ones. A similar interaction between ratio and congruency was found in recent studies with adults (e.g., Braham et al, 2018;Reynvoet et al, 2021). As in Reynvoet et al 's study, the present finding may be explained by a ceiling effect in fully congruent trials and the low accuracy in incongruent trials, especially in fully incongruent ones.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There was a ratio effect on accuracy for fully incongruent trials, but not for congruent ones. A similar interaction between ratio and congruency was found in recent studies with adults (e.g., Braham et al, 2018;Reynvoet et al, 2021). As in Reynvoet et al 's study, the present finding may be explained by a ceiling effect in fully congruent trials and the low accuracy in incongruent trials, especially in fully incongruent ones.…”
Section: Discussionsupporting
confidence: 92%
“…High accuracy in fully congruent trials has been reported previously in other studies (e.g., Gilmore et al, 2013 ; Wilkey et al, 2021 ). Braham et al (2018) suggested that when trials are difficult due to the ratio being high (small differences between the two quantities), children may use other cues to solve the comparison. In the fully incongruent trials, this strategy decreased accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next (Experiment 2), we examine the influence of the number of items and density when these features are in conflict while keeping the size of the food items equal. Last, another non-numerical variable that has been shown to influence non-symbolic numerical discrimination is the convex hull, the perimeter that encompasses all of the items in a set (e.g., DeWind and Brannon, 2016;Gilmore et al, 2016;Braham et al, 2018). This variable usually covaries with other continuous as well as numerical attributes of contrasted sets in food quantity discrimination studies with fish.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were shown a stimulus set containing segregated groups of blue and yellow dots, and were instructed to respond, in separate blocks, which of the two groups was larger with respect to each feature. We chose total surface area and convex hull because they are some of the most‐frequently investigated dimensions in the number literature (e.g., area: Brannon et al., 2006; DeWind, Bonner, & Brannon, 2020; Odic et al., 2013; Tomlinson et al., 2020; convex hull: Braham et al., 2018; Clayton et al., 2015; Clayton & Gilmore, 2015; Gilmore et al., 2016; Norris et al., 2019) and additionally, these dimensions can be varied separately from one another, which allowed us to quantify each of their individual contributions. Importantly, the stimuli were identical across the three tasks, which enables us to directly compare responses to a selfsame image.…”
mentioning
confidence: 99%